Comparison of women's stress in unexplained early pregnancy loss and normal vaginal delivery - Hajar Adib-Rad; Zahra Basirat; Mahbobeh Faramarzi; Amrollah Mostafazadeh; Ali Bijani; Marmar Firozpour Bandpy (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Postpartum period and recurrent abortion are stressful conditions that affect women's mental health. Stress and depression lead to the release of stress biomarkers that may be dangerous for the mother and fetus. The aim of this study was to determine stress in the after recurrent pregnancy loss (RPL) and normal vaginal delivery (NVD) in the north of Iran. MATERIALS AND METHODS: This case-control study was done on forty women with NVD and forty women with RPL. Stress was measured through measuring serum cortisol, Perceived Stress Scale-14 (PSS-14), and the revised version of the Symptom Checklist-90 (SCL-90-R). Data were analyzed using the Statistical Package for the Social Sciences (SPSS) 22.0 software. Chi-square test, independent-samples t-test, Mann-Whitney U-test, and Pearson correlation were used to analyze the data. RESULTS: Findings showed that nonpregnant healthy women had significantly higher cortisol level than RPL women (mean ± standard deviation [SD]: 155.80 ± 84.97 ng/ml and 126.02 ± 50.44 ng/ml, P < 0.011), respectively. Furthermore, they had higher PSS-14 and SCL-90 scores than PRL women (mean ± SD: 25.87 ± 7.48 and 25.5 ± 9.19, P = 0.745, and mean ± SD: 1.27±0.63 and 1.20 ± 0.53, P = 0.624), respectively. CONCLUSIONS: High levels of cortisol reflect the acute stress caused by the care of the baby in women. Therefore, social support for the pregnant woman by the health-care team is an essential factor for reducing postpartum depression.